Less radical surgery for early-stage cervical cancer: To what extent do we justify it?-Our belief - Nikolaos Thomakos; Sofia-Paraskevi Trachana; Miona Davidovic-Grigoraki; Alexandros Rodolakis (Elsevier, 2016)
Cancer of the uterine cervix, following breast cancer, is the second leading cause of death among gynecological cancers in the developed world. Traditionally, surgical management of early-stage cervical carcinoma is considered as a "sterilizing" procedure, since the uterus is removed. Nowadays, because of the postponement of childbearing to an older age, women younger than 45 years old who are diagnosed with early-stage cervical cancer have a strong desire to preserve fertility. Radical trachelectomy (vaginal or abdominal route) is used for fertility preservation in cases of early-stage (International Federation of Gynecology and Obstetrics Stages IA-IB1) cervical carcinomas with remarkable oncological and obstetrical outcomes. However, less radical approaches for ideal candidates may prove safe when fertility preservation is probably feasible.